Tinjauan Ilustrasi Pada Desain Kemasan "Teh Tjap Gardoe" Ditinjau dari Elemen Visual - Indriati Suci Pravitasari (Jurnal Desain Komunikasi Visual Asia, 2023)
This study examines the visual packaging of Tjap Gardoe tea. The local tea product is studied to find out whether the visual meaning contained in the visual of the Tjap Gardoe tea packaging, and whether the visual meaning has something to do with the social background in it. This study used a descriptive research method with a qualitative approach using data collection techniques from literature and observation.